(untitled) (Biological Sciences - PJSIR, 1997)
Antifungal activityoftheplantT. ammi (L.) Sprague,wascarriedoutagainstfungi,A.niger; A.flavus, F. solani, A. alternata and Helminthosporium sp, as test organisms. Different parts of the plant were extracted in various solvents andzoneofinhibitionmethod wasusedtodetectthefungi-toxicactivity.Amongall,particularlyethanol (95%)extract of the seeds was moderately effective against test fungi: benzeneandpetether extracts also showed someactivity and root extracts in water, alcohol and acetone showed stimulating activity.